Perbedaan Padat Tebar Ikan Nilem Pada Sistem Polikultur Udang Galah (Macrobranchium rosenbergii) dan Ikan Nilem (Osteochilus vittatus) - eri setiadi; fia sri mumpuni; Rosmawati Rosmawati; Muhammad Rizki Maulana (JURNAL MINA SAINS, 2018)
This research aims to determine the growth and survival rate of Giant Freshwater Prawns and Nilem fish are reared in polyculture system with different of stocking density of Nilem fish. Completely Randomized Design (CRD) with 3 treatments and 3 replications were used in this experiment, the different stocking density of Nilem fish as a treatments were as followed: A) 25 fish / m2; B) 50 fish / m2; and C) 75fish / m2 while stocking density of Giant Freshwater Prawn was 20 prawn / m2 for all treatmets. Culture period was 3 months, the waste of fish was maintaned using media filter (physical and biological) in recirculation system. The parameters such as survival, growth, and water quality were observed. The results of this study were consisted of survival rate and growth. The survival rate  of Giant Freshwater Prawn the highest was 59,76% (A), and the lowest was 44,29% (C), while Nilem fish the highest was 65% (A), and the lowest was 43.56% (C). The results of fish growth consist of absolute length, absolute weight and SGR. Absolute length of Giant Freshwater Prawn the highest was 3.09 cm (A), and the lowest was 2.38 cm (C). Nilem fish the highest was 8.63 cm (A),  and the lowest was 6.28 cm (C). The absolute weight of  Giant Freshwater Prawn the highest was 8.83 g (A), and the lowest was 5.94 g (C). Nilem fish the ighest was 10.02 g (A), and the lowest was 4.49 g (C), SGR of Giant Freshwater Prawn the highest was 1.71% (A), and the lowest was 1.33% (C). Nilem fish the highest was 9.56% (A),and the lowest was 8.31% (C). Based on these data,  A treatment was the best where according to ANOVA and Tukey's test revealed that A treratment showed significantly different (P<0.05) from B and C treatments Key words: Nilem fish, stocking density, polyculture, Giant Freshwater Prawn